Poverty Impact of Food Price Shocks and Policies - Laborde, David; Lakatos, Csilla; Martin, Will (World Bank, Washington, DC, 2019)
In the event of large swings in world food prices, countries often intervene to dampen the impact of international food price spikes on domestic prices and to lessen the burden of adjustment on vulnerable population groups. While individual countries can succeed at insulating their domestic markets from short-term fluctuations in global food prices, the collective intervention of many countries may exacerbate the volatility of world prices. Insulating policies introduced during the 2010-11 food price spike may have accounted for 40 percent of the increase in the world price of wheat and one-quarter of the increase in the world price of maize. Combined with government policy responses, the 2010-11 food price spike tipped 8.3 million people (nearly 1 percent of the world's poor) into poverty.